Characterization of Humidity Sensing of Polymeric Graphene-Quantum-Dots composites incorporated with silver nanowires - Nguyen Nang, Dinh; Long, Lam Minh; Thu, Hoang Thi; Phong, Huynh Tri; Trung, Tran Quang (VNU Journal of Science: Mathematics - Physics, 2017)
Graphene quantum dots (GQDs) were synthesized and incorporated with polyethylenedioxythiophene:poly(4-styrenesulfonate) (PEDOT:PSS), Ag  nanowires (AgNWs) to form a composite that can be used for enhancement of relative humidity (RH%) sensing. The composite films contained bulk heterojunctions of AgNW/GQD and AgNW/PEDOT:PSS. The sensors made from the composites responded well to relative humidity in a range from 10% to 50% at room temperature. With  an AgNWs content ranging from 0.2 wt.% to 0.4 wt.%  and 0.6 wt.%, the sensitivity of the relative humidity sensing devices based on AgNWs-doped GQDs+PEDOT:PSS composites was increased from 5 . 5% to 6.5 % and 15.2 %, respectively. The response time of the composite sensors was much improved due to AgNWs doping in the composites. For the 0.6 wt.% AgNWs-doped GQDs+PEDOT:PSS films, the best value of the recovery time was found to be of 30 s.